2010
DOI: 10.1038/pcan.2010.6
|View full text |Cite
|
Sign up to set email alerts
|

ELAC2 polymorphisms and prostate cancer risk: a meta-analysis based on 18 case–control studies

Abstract: Polymorphisms in the elaC homolog-2 (ELAC2)/HPC2 gene have been hypothesized to alter the risk of prostate cancer. However, the results of the related published studies remained conflicting. We performed a meta-analysis of 18 studies evaluating the association between ELAC2 Ser217Leu and Ala541Thr polymorphisms and prostate cancer risk. Overall, ELAC2 Leu217 allele was associated with increased prostate cancer risk as compared with the Ser217 allele (odds ratio (OR)=1.13, 95% confidence interval (CI): 1.03–1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…A meta-analysis showed that the Glu allele for the Asp541Glu polymorphism was associated with an increased risk in Caucasians[65], whereas a small Japanese study suggested a protective effect for Gln/Gln genotype[66]. Another meta-analysis on elaC homolog-2 ( ELAC2 ) gene/HPC2 at 17p11 indicated that the Ser allele of Ser217Leu and the Ala allele of the Ala541Thr polymorphisms significantly increased prostate cancer risk in Asians but had only marginal impact in Caucasians[67]. The Gln allele of the Arg399Gln polymorphism of the X-ray repair cross-complementing group 1 ( XRCC1 ) gene may be associated with a higher prostate cancer risk in Asians but not in Caucasians[68],[69].…”
Section: Nutrition Factors and Genetic Susceptibility Of Prostate Canmentioning
confidence: 99%
“…A meta-analysis showed that the Glu allele for the Asp541Glu polymorphism was associated with an increased risk in Caucasians[65], whereas a small Japanese study suggested a protective effect for Gln/Gln genotype[66]. Another meta-analysis on elaC homolog-2 ( ELAC2 ) gene/HPC2 at 17p11 indicated that the Ser allele of Ser217Leu and the Ala allele of the Ala541Thr polymorphisms significantly increased prostate cancer risk in Asians but had only marginal impact in Caucasians[67]. The Gln allele of the Arg399Gln polymorphism of the X-ray repair cross-complementing group 1 ( XRCC1 ) gene may be associated with a higher prostate cancer risk in Asians but not in Caucasians[68],[69].…”
Section: Nutrition Factors and Genetic Susceptibility Of Prostate Canmentioning
confidence: 99%
“…For prostate cancer, the most intensively investigated associations have related to genes in the following pathways: adhesion molecules (CDH1); androgen metabolism (AR, ESR2, SRDA2,); angiogenesis (VEGF) angiotensin conversion (ACE); baseexcision repair (XRCC1); inflammation and immune response (IL8, IL10, MSR1, PTGS2, TNF); inhibition of cell growth (FGFR4, TGFB1, TGFBR1); insulin-like growth factor metabolism (IGF1, IGFBP3); one carbon metabolism (MTHFR, diverse genes139); oxidative response (MnSOD, hOGG1); substrate metabolism (CYP1A1, CYP3A4, CYP17, GSTM1, GSTT1, GSTP1, NAT1 and NAT2, UGT2B17); vitamin D metabolism (VDR); and, common variants of genes for which rare mutations are associated with increased cancer risk (ELAC/HPC2, RNASEL, TP53, MDM2,) [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. In general, the results of candidate gene studies have been inconclusive, for reasons discussed in many interpretations [51,52].…”
Section: Role Of Single Nucleotide Polymorphismmentioning
confidence: 99%
“…The rs5030739 polymorphism of ELAC2 was one of the earliest candidates as a prostate cancer risk SNP [32] . Four studies investigated an association of rs5030739 with symptomatic BPH [33–36] .…”
Section: Evidence Synthesismentioning
confidence: 99%